The Influence of Service Quality and Product Price on Customer Satisfaction at AB Chicken, Cirebon Regency - Natulisiya, Resa Uni; Fatmasari, Dewi; Fanther, Refaldo (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2025)
The world economy, including the food industry, is experiencing very rapid development in this era of globalization. Understanding customer desires at low prices is key to being able to outperform competitors. This study was conducted with the aim of determining customer satisfaction at the AB Chicken fast food restaurant in Cirebon Regency which is influenced by the variables of service quality and product price. Purposive sampling , a type of associative quantitative research, is the sampling strategy chosen for this study. The data used in the study are primary data from a sample of one hundred respondents who are customers of AB Chicken fast food in Cirebon Regency. Multiple linear regression analysis is method Which used. Findings study disclose that quality service (X1) And price product (X2) own influence in a way positive And significant to satisfaction customer (Y). Besides That, findings more further demonstrate that in AB Chicken Regency Cirebon, satisfaction consumer can influenced by quality services and product prices simultaneously